Treating Bladder Cancer: Engineering of Current and Next Generation Antibody-, Fusion Protein-, mRNA-, Cell- and Viral-Based Therapeutics - Bogen, Jan P.; Grzeschik, Julius; Jakobsen, Joern; Bähre, Alexandra; Hock, Björn; Kolmar, Harald (Frontiers in Oncology, 2021)
Bladder cancer is a frequent malignancy and has a clinical need for new therapeutic approaches. Antibody and protein technologies came a long way in recent years and new engineering approaches were applied to generate innovative therapeutic entities with novel mechanisms of action. Furthermore, mRNA-based pharmaceuticals recently reached the market and CAR-T cells and viral-based gene therapy remain a major focus of biomedical research. This review focuses on the engineering of biologics , particularly therapeutic antibodies and their application in preclinical development and clinical trials, as well as approved monoclonal antibodies for the treatment of bladder cancer. Besides, newly emerging entities in the realm of bladder cancer like mRNA, gene therapy or cell-based therapeutics are discussed and evaluated. As many discussed molecules exhibit unique mechanisms of action based on innovative protein engineering, they reflect the next generation of cancer drugs. This review will shed light on the engineering strategies applied to develop these next generation treatments and provides deeper insights into their preclinical profiles, clinical stages, and ongoing trials. Furthermore, the distribution and expression of the targeted antigens and the intended mechanisms of action are elucidated.